3D printing as an adjunct to complex airway assessment. Issue 2 (8th November 2016) - Chambers, David; Tol, Govind W.; Smurthwaite, Glyn J.; Herwadkar, Amit V.
Summary: A patient with known neurofibromatosis type 1 (NF1) who presented for urgent spinal surgery was predicted to have a difficult airway due to a large craniofacial neurofibroma. From a three dimensional (3D) computed tomography (CT) reconstruction of his airway, a 3D printed model was manufactured. The 3D model aided the peri‐operative planning of the patient's airway management, and is the first published report of its kind.